Notonagoro dan Religiusitas Pancasila - Syarif Hidayatullah (Jurnal Filsafat "WISDOM", 2006)
When he paid close attention to dynamic of the members ofa religious community interpretation toward Pancasila, Notonagorohad an idea his compromise and philosophical point of view thatshow strongly wisdom and knowing glance deeply, namely:religiosity of Pancasila. Although he never mention this term,religiosity of Pancasila, at all, but its contain and meaning wasstrongly pictured in his thinking about three principles ofPancasila, viz.: cultural principle, religiosity principle, and affairsof state principle. Religiosity of Pancasila was not intend to thatPancasila then become “a religion” for all peoples. Religiosity ofPancasila, which was formulated from Notonagoro’s thingkiing,was a functionalizing  of spiritual principle of Pancasila.